Sign System Untuk Masyarakat Di RT 04 RW 05 Dukuh Beran, Dusun III, Desa Dibal, Kecamatan Ngemplak, Kabupaten Boyolali, Jawa Tengah - Yudi Wibowo; Deny Nikmatul Rosita; Magrib Pardjer; Faqih Raida Salma Al Fawas; Raden Kusuma Candra Gusti Aji (Universitas Sahid Surakarta, 2022)
Abstract The design of this sign system aims to help the community, visitors and newcomers. The sign system that is being worked on is a signpost as a marker of regional boundaries and a pictogram to give instructions on a place or regulation when in the prayer room. The signs made are RT barrier signs. This sign was made because the previous sign still looked unattractive and also because there was a request from the local RT asking to be replaced. This pictogram was made because in the Al-Mak'mur prayer room there is no pictogam as a guide while in the prayer room so that visitors who come are still confused when they are in the prayer room. The method used is the design method. The design method used in the design of making pictograms and signs is RT 04 RW 05 Hamlet Beran, Hamlet III, Dibal Village, Ngemplak District, Boyolali Regency. By making these pictograms and signposts, people can more easily find places and RTs to go to. Also helps inform visitors to the prayer room about the instructions when in the prayer room.